Employees’ perception of green corporate social responsibility and green behavior in nonprofit organizations: The case of Saudi Arabia - Sager Alharthi; Amirah Alghamdi (Problems and Perspectives in Management)
The purpose of this study is to investigate the perception of green corporate social responsibility (GCSR) among employees and its consequent effects on sustainability behaviors within nonprofit organizations (NPOs). Additionally, it examines how engagement in environmentally responsible behaviors influences organizational elements such as communication strategies, leadership support, and the implementation of sustainability initiatives. Through questionnaires, data were gathered from 355 NPO employees in Saudi Arabia to quantitatively survey their perceptions, attitudes, and engagement related to environmental sustainability practices within their organizations. The information was examined using exploratory factor analysis, confirmatory factor analysis, and structural equation modeling. Employee perception of GCSR was found to have a positive and significant impact on awareness of environmental sustainability, attitudes toward environmental sustainability, and engagement in environmentally responsible behaviors, with a high coefficient. Moreover, engagement in environmentally responsible behaviors was discovered to exert a positive and significant impact on communication strategies, leadership support, and implementation of sustainability behavior, with a high coefficient. These findings have practical implications for NPO managers aiming to enhance their GCSR strategies, promote environmental sustainability among employees, and integrate sustainability into their core operations.